2006
DOI: 10.1021/es050094i
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diesel Fuel Sulfur on Nanoparticle Emissions from City Buses

Abstract: Particle emissions from twelve buses, operating alternately on low sulfur (LS; 500 ppm) and ultralow sulfur (ULS; 50 ppm) diesel fuel, were monitored. The buses were 1-19 years old and had no after-treatment devices fitted. Measurements were carried out at four steady-state operational modes on a chassis dynamometer using a mini dilution tunnel (PM mass measurement) and a Dekati ejector diluter as a secondary diluter (SMPS particle number). The mean particle number emission rate (s(-1)) of the buses, in the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 14 publications
5
68
0
Order By: Relevance
“…The higher sulfur content in LSD can be converted to sulfuric acid or sulfate in the combustion and dilution processes. These compounds can be removed by a thermal denuder and are considered as the volatile substances (Maricq et al 2002;Ristovski et al 2006). Moreover, sulfuric acid can also promote the nucleation of organic compounds, leading to more volatile substances in the particulate samples (Shi and Harrision 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The higher sulfur content in LSD can be converted to sulfuric acid or sulfate in the combustion and dilution processes. These compounds can be removed by a thermal denuder and are considered as the volatile substances (Maricq et al 2002;Ristovski et al 2006). Moreover, sulfuric acid can also promote the nucleation of organic compounds, leading to more volatile substances in the particulate samples (Shi and Harrision 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that nucleation mode particles with diameter less than 50 nm are mostly formed from volatile hydrocarbon or sulfuric acid in the dilution process, thus these particles contain a higher mass fraction of volatile substances. On the other hand, particles with much larger size have fractal-like structure which provides more pores and intra-particle cavities for the condensation and adsorption of volatile substances (Kerminen et al, 1997;Ristovski et al, 2006), leading to an increase of the volatile fraction in these particles. Similar result was also found by Kerminen et al (1997) and Zhang et al (2009) who used low-pressure impactor in their investigations.…”
Section: Mass-based Investigation Of Particle Volatilitymentioning
confidence: 99%
“…However, for the LSD, the percentage of volatile particles exhibits monotonic increase with engine load. At low engine load, due to lower incylinder gas temperature, there is a larger amount of unburned hydrocarbon and lubricating oil in the exhaust gas which could be converted to volatile particles or condense on existing soot agglomerates (Ning et al, 2004;Ristovski et al, 2006;Mustafi et al, 2010), leading to an increase in particle volatility. The increase in volatility under high engine load is uncommon but has also been observed by Meyer and Ristovski (2007) through a VH-TDMA (volatilization and humidification tandem differential mobility analyzer) investigation on emissions from a six-cylinder diesel engine fueled with commercial 500-ppm-wt sulfur diesel fuel.…”
Section: Mass-based Investigation Of Particle Volatilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its role in varying the rates of nucleationcondensation processes, sulfur content in fuel and lubricating oil can also have an important role in the mass and number of fine PM emitted from mobile sources. Overall, studies have consistently reported that the presence of sulfur in fuel and lubricating oil increase the mass of emitted fine PM, but their size distributions vary depending on the availability of organic and soot fractions in the exhaust (Vaaraslahti et al, 2005;Ristovski et al, 2006). Although sulfate typically constitutes a small fraction of total emitted fine PM (particularly for diesel-powered vehicles without a diesel particle filter), the presence of sulfur in the fuel increases the total mass of fine PM emitted due to increases in the rate of nucleation-condensation processes.…”
Section: Pm25 Emissionsmentioning
confidence: 99%